Rajhman o vlogi žensk v Cerkvi - Pevec Rozman, Mateja (Edinost in dialog, 2025)
In the aftermath of the Second Vatican Council, the question of the role of the laity, particularly of women within the Church emerged as one of the most urgent pastoral and theological concerns, closely linked to the issue of formation. The Slovenian theologian, pastoral scholar, literary historian, and philologist Jože Rajhman, PhD (1924–1998), active precisely in this period, devoted significant attention to this question. This article provides the first systematic study of Rajhman’s understanding of the role of women in the Catholic Church, based on both his published writings and unpublished archival material preserved in the Archdiocesan Archives of Maribor (AAM). Methodologically, the article combines textual analysis of published works with critical examination of primary archival sources (manuscripts and typescripts, notes, and drafts), focusing on two archival units of Rajhman’s estate (AAM, boxes 5 and 9). Particular attention is given to his spiritual reflections and exhortations addressed to women, nuns, and catechists, as well as to his engagement with the Cistercian priest Leopold Bertsche (1915–1997), a little-known figure in Slovenia, whose thought Rajhman frequently referenced. Four shorter published articles on the “women’s question” are analysed, following a thematic and chronological framework with exception of the last. The findings reveal Rajhman’s consistent openness toward the inclusion and active participation of women in the life and mission of the Church, with special emphasis on their theological formation and role as catechists, key collaborators in the Church’s evangelizing mission. This orientation places him among the few Slovenian theologians who advanced, within the local context, one of the major novelties of the Second Vatican Council. The originality of the article lies in its analysis of Rajhman’s hitherto unexplored legacy and in positioning his reflections within the broader theological discourse of the Second Vatican Council. By highlighting previously unknown aspects of his thought, the study not only contributes to Slovenian Church historiography but also establishes a foundation for further scholarly inquiry into the reception of the Council, particularly regarding the role and status of women in the Church.
Keywords: catechists; Cerkev; Church; drugi vatikanski koncil; katehistinje; laiki; laity; Second Vatican Council; the role of women; vloga žensk